Influence of Psychological Nursing Procedure on Negative Emotion, Stress State, Quality of Life and Nursing Satisfaction in Patients with Lung Cancer Radical Operation - Yu, Yizhi; Xia, You; Fan, Xiaoyan; Chen, Yong; Li, Chengjuan; Zhang, Jing (Frontiers in Surgery, 2022)
Objective To discuss the influence of psychological nursing procedure on negative emotion, stress state, quality of life and nursing satisfaction in patients with lung cancer radical operation. Methods 106 patients with lung cancer who underwent radical resection in our hospital from September 2019 to September 2021 were selected. According to the intervention time, patients were divided into Group A and Group B, with 53 cases in each group. Group A received routine nursing, Group B used psychological nursing procedure on the basis of Group A. The negative emotions, stress state, quality of life and nursing satisfaction of patient were observed. Results Self-rating anxiety scale and self-rating depression scale scores of Group B were lower than Group A (P < 0.05). The levels of norepinephrine, epinephrine and cortisol in Group B were lower than Group A (P < 0.05). Generic quality of life inventory-74 scores of Group B were higher than Group A (P < 0.05). The nursing satisfaction of Group B (88.68%) was higher than Group A (73.58%) (P < 0.05). Conclusion Psychological nursing procedure is conducive to reducing the negative emotion, relieving stress reaction, improving the quality of life, increasing nursing satisfaction of patients with lung cancer radical operation.